Knowledge, Attitude and Practice Regarding Ramadan Fasting and Related Determinants in Patients with Type 2 Diabetes at a Saudi Diabetes Clinic - Alsunni, Ahmed Abdulrahman (Diabetes Metab Syndr Obes, 2020)
OBJECTIVE: This study was carried out in type 2 diabetes mellitus (T2DM) patients to assess their knowledge, attitude and practice about fasting during Ramadan and to identify the sociodemographic determinants of the knowledge, attitude and practice. METHODS: A total of 107 T2DM patients were interviewed at a diabetes clinic in the Eastern Saudi Arabia. A questionnaire containing knowledge, attitude and practice questions about fasting during Ramadan was used to collect data. Data about age, gender, city of residence, nationality, level of education, and history of diabetes in family were also collected. Descriptive and inferential statistics were carried out using IBM-SPSS Version 21. RESULTS: The mean total score for knowledge, attitude and practice was 16.5 ±3.72 (out of 27). The individual scores for knowledge, attitude and practice were: 9.67±2.53 (out of 16), 4.10±1.28 (out of 6), and 2.77±1.08 (out of 5), respectively. Gender (OR: 4.08, 95% CI: 1.05,15.79 and p<0.041), education (OR: 0.068, 95% CI: 0.008,0.594, p<0.015) and family history (OR: 5.086, 95% CI: 1.095, 23.630 p<0.038) were identified as independent determinants of the total score. CONCLUSION: Gender, Family history of diabetes and Education are determinants of knowledge, attitude and practice regarding fasting during Ramadan in the T2DM patients. A significant knowledge practice gap exists that necessitates further strengthening of the Pre-Ramadan education program for T2DM patients.